RECONCEPTUALIZING LOYALTY: IBN KHALDUN’S THOUGHT AND ITS RELEVANCE TO MODERN MANAGEMENT - Sari Fitri; Zainuddin Zainuddin; Adripen Adripen (Peminat Ilmu Ushuluddin, 2025)
The loyality has become a strategic issue in modern management, particularly amid the dynamics of globalization, digitalization, and the growing prevalence of transactional employment relationships. This article aims to analyze the concept of loyalty in Ibn Khaldun’s thought through the notion of ‘aṣabiyyah (social solidarity) and to examine its relevance within the context of contemporary management and human resource management. This study employs a qualitative literature-based approach by critically examining Ibn Khaldun’s seminal work, Muqaddimah, alongside modern management literature addressing loyalty, organizational commitment, and leadership. The findings indicate that loyalty in Ibn Khaldun’s perspective is dynamic and deeply rooted in social bonds, justice, ethical leadership, and collective purpose, which conceptually corresponds with the notion of affective commitment in modern management theory. However, this study also identifies inherent tensions between morally grounded solidarity as articulated in ‘aṣabiyyah and contemporary managerial practices that tend to emphasize material incentives, individualism, and instrumental rationality. The main contribution of this article lies in the development of a conceptual framework that integrates Islamic values—such as justice, ihsān, and deliberation (shūrā)—into modern human resource management as an alternative approach to strengthening employee loyalty and organizational commitment in the digital and globalized era. Accordingly, Ibn Khaldun’s thought is shown to be not merely of historical significance, but also to offer an ethical and humanistic foundation for contemporary organizational management.